Pelatihan “Remaja Bijak” terhadap Kecenderungan Perilaku Prososial Remaja - Maria Theresia; Esti Hayu Purnamaningsih (Faculty of Psychology, Universitas Gadjah Mada, 2019)
Behavioral problems in adolescents at school become a phenomenon that is increasingly seen nowadays. Prosocial behavior is important for adolescents to carry out their social functions well. One important aspect that influences the tendency of prosocial behavior is emotion. The study’s objective was assessing the role of